2012
DOI: 10.1055/s-0038-1623620
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of dogs via chromosomal analysis and array-based comparative genomic hybridization (aCGH)

Abstract: SummaryThe results of cytogenetic and molecular cytogenetic investigations revealed similarities in genetic background and biological behaviour between tumours and genetic diseases of humans and dogs. These findings classify the dog a good and accepted model for human cancers such as osteosarcomas, mammary carcinomas, oral melanomas and others. With the appearance of new studies and advances in canine genome sequencing, the number of known homologies in diseases between these species raised and still is expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…In humans recurrent chromosome aberrations were reported that are shared by specific cancers [24]. In dogs, cytogenetic studies are complicated by the complex canine karyotype [25], therefore, the genome analysis of canine neoplasms greatly benefited from the development of CGH microarrays (aCGH) [26]. Also, copy-number differences in the germline of different breeds have been discovered by the use of aCGH [27].…”
Section: Introductionmentioning
confidence: 99%
“…In humans recurrent chromosome aberrations were reported that are shared by specific cancers [24]. In dogs, cytogenetic studies are complicated by the complex canine karyotype [25], therefore, the genome analysis of canine neoplasms greatly benefited from the development of CGH microarrays (aCGH) [26]. Also, copy-number differences in the germline of different breeds have been discovered by the use of aCGH [27].…”
Section: Introductionmentioning
confidence: 99%
“…Bei humanen Tumoren sind außerdem tumorspezifische chromosomale Veränderungen beschrieben worden (Beroukhim et al, 2010). Da cytogenetische Untersuchungen beim Hund durch die Vielzahl von Chromosomen erschwert sind, eignen sich hier vor allem Verfahren der vergleichenden genomischen Hybridisierung mittels Microarrays (aCGH) (Thomas et al, 2007;Muller et al, 2012). Auf diese Weise konnten erst kürzlich umfangreiche zwischen Hund und Mensch überlappende CNI-Regionen beim Darmkrebs identifiziert werden (Tang et al, 2010).…”
Section: Introductionunclassified